Electroconvulsive therapy and its relationships with clinical characteristics and quality of life in Chinese psychiatric patients. (30th December 2016) - An, Feng-Rong; Zhang, Ling; Zhang, Qing-E.; Ungvari, Gabor S.; Ng, Chee H.; Chiu, Helen F.K.; Wu, Ping-Ping; Jin, Xin; Li, Lu; Lok, Grace K.I.; Xiang, Yu-Tao
Abstract: Little is known about the pattern of electroconvulsive therapy (ECT) use in the clinical population in China. This study examined the percentage of ECT use and its association with clinical characteristics and quality of life (QOL) in a psychiatric center in China that caters for a population of 20 million. A total sample of 1364 inpatients was consecutively recruited for the study. Demographic and clinical data including the use of ECT were collected. Psychopathology, activity of daily living and QOL were measured using standardized instruments. The percentage of ECT use was 52.1% in the whole sample; 53.4% in major depression, 57.8% in bipolar disorder, 57.0% in schizophrenia and 32.4% in other diagnoses. There was no significant difference between the ECT and non-ECT groups in any domain of QOL. Multivariate analyses revealed that ECT was independently associated with the diagnoses of major depression, bipolar disorder and schizophrenia, physical restraint, severe aggression, better activity of daily living skills, more frequent use of antipsychotics and less frequent use of benzodiazepines. The percentage of ECT use was much greater in a major psychiatric center in China than those reported from other parts of the world. Use of ECT had no influence on the short-term QOL. Further investigations are warranted to explore the reasons for the high percentage of ECT use. Highlights: The frequency of electroconvulsive therapy (ECT) use was 52.1%. Use of ECT had no influence on the short-term QOL.